1, 8‐Diphenyl‐9, 10‐Bis(arylethynyl)phenanthrenes: Synthesis, Distorted Structure, and Optical Properties. Issue 25 (10th April 2018) - Konishi, Akihito; Morinaga, Atsushi; Fukuhara, Gaku; Nishijima, Masaki; Mori, Tadashi; Kida, Toshiyuki; Yasuda, Makoto
Abstract: The synthesis and optical properties of 1, 8‐diphenyl‐9, 10‐bis(arylethynyl)phenanthrenes, which are distorted phenanthrenes, are reported. The presence of the two phenyl groups at the 1, 8‐positions of phenanthrene significantly distorts the molecular geometries, as was evidenced by X‐ray crystallography. The congested substitution pattern in the K region results in a distorted aromatic framework, which leads to a redshift in the emission spectrum. These observations are in stark contrast to 9, 10‐bis(phenylethynyl)phenanthrene with no phenyl groups at the 1, 8‐positions. A large Stokes shift suggested extensive structural relaxation between the phenyl and arylethynyl units in the excited state, which was supported by theoretical calculations. Abstract : Distorted phenanthrenes : The synthesis and optical properties of 1, 8‐diphenyl‐9, 10‐bis(arylethynyl)phenanthrenes, which are distorted phenanthrenes, are reported. A congested substitution pattern in the K region resulted in a distorted aromatic framework, which led to a redshift in the emission spectrum. A large Stokes shift suggested an extensive degree of structural relaxation between the phenyl and arylethynyl units in the excited state (see figure).